Polarographic Reduction of Ethylene Glycol at d.m.e. - Kamal, K.P.; Singh, S.P.; Mujitaba, S.G. (Asian Journal of Chemistry, 2010)
Polarographic reduction of ethylene glycol in unbuffered supporting electrolytes like molar potassium chloride and saturate potassium sulphate has been carried out at dropping mercury electrode. A single d.c. step was observed. The E1/2 in 1 M KCl solution was found to be -0.22 V vs. SCE, whereas in saturated potassium sulphate, it is 0.26 V vs. SCE The appearence of a single d.c. step suggests that only one hydroxyl group of ethylene glycol suffers cathodic reduction giving most likely ethanol.